PENGARUH FAKTOR DUKUNGAN UNIVERSITAS DAN KEPRIBADIAN PROAKTIF TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Qausar Geubrina Rizki, Megawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract:This study aims to measure the effect of university Support Factors and Proactive Personality on Entrepreneurial Intention of Economic and Business Faculty of Syiah Kuala University undergraduate student’s. The sample used in this study were active undergraduate student’s in odd semester 2017/2018 is totaling 240 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Probability Sampling. multiple regression is used as an analytical methodBased on the results of Multiple Linear Regression analysis, indicating that the University Support Factor has a positive effect on Entrepreneurial Intentions and Proactive Personality has a positive effect on Entrepreneurial Intention.  Keywords: University Support Factors, Proactive Personality, Entrepreneurial Intention, Multiple Linear Regression.